WCER Research Highlights, Vol. 21 No. 2, Winter 2010 - Baker, Paul (My University, 2010)
Table of Contents: A New Era for the Strategic Management of Human Capital; Developing as a Writer; Surveys of Learning Reveal Strengths, Weaknesses; Using Teacher Performance Assessments for Human Capital Management.